POROUS ABSORBER OF NOISE CONTROL PANEL MANUFACTURING FROM COCONUT FIBER AND PET WASTE FIBER (SHOODY FIBER) - Saeful Islam; Mochammad Danny Sukardan; Eva Novarini; Farri Aditya (Arena Tekstil, 2018)
Noise exposure could have a negative effect on humans in the form of hearing loss, sleep disturbances, high blood pressure and heart problems, respiratory and metabolic disorders, mental health disorders and cognitive impairment. So noise control efforts are needed. Noise control efforts was carried out by making porous absorber of noise control panel by utilizing abundant natural resources in the form of coconut fiber, utilization of PET fiber from textile waste (shoody fiber) and low melt polyester. From the test results obtained that all combinations meet the criteria for sound absorption from class B to E, and the results of maximum absorption are 0.88 absorption coefficient obtained by a combination of three layers between 50% coconut fiber, 20% shoody fiber and 30% low melt polyester.